The Political Economy of Corporate Control - Enrico Perotti; Ernst-Ludwig von Thadden (Tinbergen Institute, 2005)
In a democracy, a political majority can influence both the corporategovernance structure and the return to human and financial capital.We argue that when financial wealth is sufficiently diffused, thereis political support for a strong governance role for dispersed equitymarket investors, and low labor rents. When financial wealth is concentrated,a political majority prefers high labor rents and a strongergovernance role for banks or large investors, even at the cost of profits.The intuition is that labor claims are exposed to undiversifiable risk,so voters with low financial stakes prefer investors who choose lowerrisk strategies. The model may explain the ”great reversal” phenomenonin the first half of the 20th century (Rajan and Zingales, 2003).We argue that in several financially developed countries a financiallyweakened middle class became concerned about labor income risk associatedwith free markets and supported a more corporatist financialsystem. We offer suggestive evidence using post WW1 inflationaryshocks as the source of identifying exogenous variation.
Keywords: G2; G3; P16; 330; Corporate governance; political economy; bank control; investor protection